2015
DOI: 10.1080/07929978.2015.1067411
|View full text |Cite
|
Sign up to set email alerts
|

Induction of tetraploidity with antimicrotubule agents in oriental melon (Cucumis melo var. Makuwa)

Abstract: Polyploidy induction is an important method for the innovation of germplasm resources because polyploid plants have superior characteristics to diploid ones. In this paper, oriental melon (Cucumis melovar. makuwa) tetraploids were induced by treating the apical meristem of seedlings with oryzalin, amiprophos-methyl (APM) and colchicine. The results showed that each of these three antimicrotubule agents could induce the formation of tetraploid oriental melon, but oryzalin and APM showed higher efficiencies of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…The efficiency of polyploidization achieved using oryzalin reached up to 15%. Similar to the current study, a polyploidization rate of up to 11.11% was obtained in oriental melon when oryzalin was used as an antimitotic agent [20].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The efficiency of polyploidization achieved using oryzalin reached up to 15%. Similar to the current study, a polyploidization rate of up to 11.11% was obtained in oriental melon when oryzalin was used as an antimitotic agent [20].…”
Section: Discussionsupporting
confidence: 88%
“…For instance, in Cucumis melo L., polyploids were successfully induced using oryzalin, where the obtained polyploid plants exhibited substantial morphological changes in seeds, leaves, and stomata compared with the diploid mother plants [18]. A similar study on the same species reported a higher total soluble solid content in tetraploid fruits than in diploid fruits [20]. In Cucumis sativus L., polyploids were produced using colchicine that displayed larger leaf size, flower diameter, stoma size, pollen grains, and more chloroplast numbers in guard cells [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyploidization is one of the most effective approaches to improving fruit quality. In the previous studies, autotetraploid plants were shown to bear much larger fruit; for example, autotetraploid trees of apple [40] and banana [38], and autotetraploid plants of muskmelon [8,41]. On the contrary, the average fruit size of autotetraploid pears is approximately the same as that of diploids, though the autotetraploid fruit grows quicker than diploids during the early stages [10].…”
Section: Discussionmentioning
confidence: 99%